Does Online Access Promote Research in Developing Countries? Empirical Evidence from Article-Level Data - Frank Müller-Langer; Marc Scheufen; Patrick Waelbroeck (European Commission, Joint Research Centre (JRC), 2018)
Universities in developing countries have rarely been able to subscribe to academic journals in the past. The “Online Access to Research in the Environment” initiative (OARE) provides institutions in developing countries with free online access to more than 5,700 environmental science journals. We analyze the effect of OARE on scientific output in five developing countries. We apply difference-in-difference-in-differences estimation using a balanced panel with 161,450 observations derived from 36,202 journal articles published by authors affiliated with 2,490 research institutions. Our approach allows us to explore effects across scientific fields, i.e. OARE vs. non-OARE fields, within institutions and before and after OARE registration. We benefit from the fact that variation in online access to scientific literature is exogenous at the level of scientific fields. Additional self-selection issues are dealt with by using an endogenous binary variable model estimated by a Bayesian Markov-Chain-Monte-Carlo method. We provide evidence for a positive marginal effect of online access via OARE on publication output that ranges between +48% and +57%. Our results suggest that the most productive institutions benefit the most from OARE while the least productive institutions barely benefit from it.
Keywords: L17; O33; 330; online access; scientific productivity; difference-in-difference; Bayesian Markov Chain monte carlo estimation